KABUT ASAP & KEJAHATAN LINGKUNGAN - Munir, Abdul (Sisi Lain Realita, 2016)
Smoke fog is rest of from burning forest and peat farm really as big debacle for human. Undeniably again mentioned of tail from exploitation forest by company of permit handle. There is ambiguity if careful State role in this case. One side of policy forestry sector give the amenity portion for investor in getting permit. while on the other side as Body politic, State impress unable to criminalization of Perpetrators of forest crime.